Identidad y el patrimonio cultural. El caso de los sitios arqueológicos de la Provincia de La Rioja. - Torres, Marcelo Adrián (2006)
Seen from an interdisciplinary view and from the perspective of Communication, Design and Anthropology, the project tackles with the presentation and communication of the cultural heritage with the purpose of promoting the reunion between people and the archeological locations and easy to spot historical places oriented to the sustainable tourist utilization of cultural archeological resources; encouraging the sense of cultural identity within the community, therefore going far towards a re-significance of the regional past, which stops being perceived as a past belonging to “other people” to become their own; and finally, laying the foundations for a social and tourist development of the community. The research work presented has been done within the framework of the Postgraduate Scholarship Program of the Design and Communication Studies Centre of the School of Design and Communication, Universidad de Palermo, O projeto, desde uma visão interdisciplinar e partindo da perspectiva da Comunicação, do Design e da Antropologia, aborda a apresentação e comunicação do patrimônio cultural com o objetivo de promover o encontro entre o público e os sítios arqueológicos e os lugares históricos de alta visibilidade, orientados ao aproveitamento turístico sustentável de recursos arqueológicos culturais; estimular o sentido de identidade cultural na comunidade, contribuindo à re- significação do passado regional, deixando de ser visto como o passado dos “outros” para ser o próprio; e finalmente, criar as bases para o desenvolvimento social e turístico da comunidade. O trabalho de pesquisa que se apresenta têm sido realizado no marco do Programa de Becas de Pós- graduação do Centro de Estudos de Design e Comunicação da Faculdade de Design e Comunicação da Universidade de Palermo. El proyecto, desde una visión interdisciplinaria y partiendo de la perspectiva de la Comunicación, el Diseño y la Antropología, aborda la presentación y comunicación del patrimonio cultural con el objetivo de promover el encuentro entre el ...